IX. Gravimetric Survey in the Mizuho Plateau-West Enderby Land Area, East Antarctica, 1969-1971 - ヨシダ, マサル; ヨシムラ, アイイチロウ; YOSHIDA, Masaru; YOSHIMURA, Aiichiro (National Institute of Polar Research, 1972)
P(論文) departmental bulletin paper